PEMANFAATAN SUMBERDAYA HUTAN DI HUTAN LINDUNG KECAMATAN ALU KABUPATEN POLMAN PROPINSI SULAWESI BARAT - . Asrianny; Muhammad Dassir; . Asrianty (Forestry Faculty of Universitas Hasanuddin, 2012)
This study aims to determine the activity of the utilization of forest resources and to know local community wisdom related to protection forest in the Alu Village areas. This research was conducted by using Rapid Rural Appraisal (RRA) method. Respondents in this study were communities living in and around the protection forest area and conducting activities in the forms of utilizing the forest resources. The observed variables were the forms of community activities in the protection forest and local community wisdom in using the forest resources. The results show that activities of villagers consist of: 1) the use of timber for home construction or repair and for fuel wood, 2) the utilization of rattan, 3) the utilization of bamboo, 4) the utilization of palm, 5) the utilization of honey bee and other forest products. In addition, local community wisdom in the utilization of forest products was found to be in the form of prevailing institutions in the village of Alu. The forms of institutions are forest harvesting institutions, forest land use institutions, and forest protection and security institutions. In general, Alu Villagers have the awareness to preserve the environment, ecological balance and sustainability of the population to be bequeathed to their generation. Yet, the wisdom is prone to turn down particularly in the institution of timber utilization. Key words: Forest resource utilization, protected forest, local wisdom, Alu Villagers